Linking cereal chemistry to nutrition: studies of wheat bran and resistant starch - Brewer, Lauren Renee (Kansas State University, 2012)
Wheat bran is high in dietary fiber. Resistant starch (RS) is considered a source of dietary fiber. Wheat bran and RS have different functional properties and may not have the same nutritional properties. This dissertation covers two areas of importance in cereal chemistry and human nutrition: wheat bran and RS. Wheat bran chemical and physical influence of nutritional components Wheat bran has become a hot topic due to positive nutritional correlations, and industrial /humanitarian needs for healthy ingredients. Evolving wheat bran into a demanded product would impact the industry in a positive way. The overall aim of this research was to understand chemical and structural composition, to provide avenues for wheat bran development as a healthy food ingredient. To achieve this goal, antioxidant properties in dry wheat milling fractions were examined, effects of wheat bran particle size on phytochemical extractability and properties were measured, and substrate fermentation was investigated. It was noted that mixed mill streams, such as mill feed, have antioxidant properties (0.78 mg FAE/g; 1.28 mg/g total antioxidant capacity; 75.21% DPPH inhibition; 278.97 [mu]mol FeSO[subscript]4/g) originating from the bran and germ fractions. Additionally, extraction of reduced particle size whole wheat bran increased measured values for several assays (185.96 [mu]g catechin/g; 36.6 [mu]g/g; 425 [mu]M TE), but did not increase volatile fatty acid production during in vitro rumen fermentation over unmilled bran. RS digestion, glycemic response and human fermentation In vitro action of enzymes on digestion of maize starches differing in amylose contents were studied. The objectives of this study were to investigate the exact role of [alpha]-amylase and amyloglucosidase in determining the digestibility of starch and to understand the mechanism of enzymatic actions on starch granules. Starch digestibility differed (30-60%) without combination of enzymes during in vitro assay. Further investigations utilized human glycemic response and fermentation with consumption of a type 3 RS without dietary fiber (AOAC method 991.43). Blood glucose response provided lower postprandial curves (glycemic index value of 21) and breath hydrogen curves displayed low incidences fermentation (40%) with consumption of the type 3 RS, due to the structure of starch and digestion by enzymatic action.
Keywords: Antioxidants; Wheat bran; Glycemic index; Resistant starch; Fermentation; Chemistry, Agricultural (0749); Food Science (0359); Nutrition (0570)